Enhancement of Training, Career Development and Motivation to the Performance of Personnel Sathar 22 Depohar 20 - Setiyawan, Agung; Pujiati, Herni (Dinasti Publisher, 2025)
This research aims to analyze the influence of training, career development and motivation on the performance of Maintenance Unit 22 (Sathar 22) Maintenance Depo 20 (Depohar 20) personnel of the Indonesian Air Force. Sathar 22 has an important role in carrying out calibration of precision measuring instruments (AUP), Ground Support Equipment (GSE), avionics testers and special aircraft testers. As the person tasked with maintaining the accuracy standards of measuring instruments, Sathar 22 faces challenges in the form of a decrease in the number of personnel due to retirement, tour of duty/tour of area (TOA/TOD), as well as various other factors that can affect the smooth maintenance and calibration of the system. This research uses a qualitative method with a descriptive approach which aims to explore the factors that influence personnel performance. The research results show that effective training acts as a long-term investment in improving the quality of human resources, so that personnel can work more competently and efficiently. Structured career development provides clear direction and goals for individuals in achieving a higher level. Apart from that, work motivation provided through incentives, awards and recognition for their performance plays an important role in increasing work morale. With good human resource management, it is hoped that Sathar 22 can achieve optimal operational effectiveness and efficiency in supporting maintenance and calibration tasks.